Effects of low‐to‐moderate alcohol supplementation on urinary estrogen metabolites in postmenopausal women in a controlled feeding study. (6th September 2017) - Mahabir, Somdat; Pfeiffer, Ruth; Xu, Xia; Baer, David J.; Taylor, Philip R.
Abstract: Heavy alcohol drinking is associated with increased breast cancer risk, but associations with low‐to‐moderate alcohol consumption are less clear and the biological mechanisms are not well defined. The objective of this study was to evaluate the effects of 8 weeks of low (15 g/d) and moderate (30 g/d) alcohol ingestion on concentrations of 15 urinary estrogen metabolites (EMs) in postmenopausal women ( n  = 51) in a controlled feeding study with a randomized crossover design. Compared to no alcohol, 15 g/day for 8 weeks had no effect on urinary EMs. However, compared to no alcohol, 30 g/day for 8 weeks decreased urinary 2‐hydroestrone (2‐OHE1) by 3.3% ( P  =   0.055) and increased 16‐epiestriol (16‐EpiE3) by 26.6% ( P  =   0.037). Trends for reduced urinary 2‐OHE1 ( P  =   0.045), reduced ratio of 2‐OH:16OH pathways ( P  =   0.008), and increased 16‐EpiE3 ( P  =   0.035) were observed as alcohol ingestion increased from 0 g to 15 g to 30 g/d. Moderate alcohol consumption for 8 weeks had modest effects on urinary concentrations of 2‐OHE1 and 16‐EpiE3 among postmenopausal women in a carefully controlled feeding study. Abstract : Recent evidence indicates that postmenopausal breast cancer risk increases with higher levels of 16‐EpiE3 and decreases with lower levels of 2‐OHE1 in different prospective cohorts. Since moderate alcohol consumption in our study of postmenopausal women increased 16‐EpiE3 and lowered 2‐OHE1, these results imply that moderate drinking may have dual effects on later breast cancer development, but this finding needs confirmation.